Patentable Subject Matter: Comparison between French and Jordanian Laws - Mohammed, Iriqat (International Journal of Humanities and Social Science Research, 2015)
The purpose of this study is to make a comparison between the patentable subject matter in French and Jordanian law in order to extract the similarities and differences to establish basic principles for Palestine. The Jordanian law is selected as it is in general the law that is applied in Palestine. Palestine is the only country in the Middle East that does not have legislations protecting intellectual property rights. However, there are sporadic laws applied in Palestine, such as the Ottomans’ law in 1910 related to copyright law and the Jordanian trademark 1952 and patent law in 1953. In 1995 the Palestinian Authority approved some legislation in the field of private law, such as civil and commercial law, but without including in it intellectual property legislation. The term intellectual property is not popular among Palestinian legislators as there are among them few experts in this field.